Effect of flow rate and condenser cooling water temperature on product yield of coconut trunk sawdust pyrolysis liquid smoke - Srisitisugiastuti B; Andi Aladin; Takdir Syarif; Lastri Wiyani (Konversi, 2024)
Liquid smoke is a product resulting from the pyrolysis of biomass waste that contains chemical compounds with various applications, such as food preservatives, natural pesticides, and raw materials for the chemical industry. Liquid smoke is a by-product of simultaneous pyrolysis. To maximize the yield of liquid smoke while minimizing mass loss that could potentially pollute the environment, the simultaneous pyrolysisreactor needs to operate under optimal condensation conditions. This study observed two condensation parameters: the flow rate and the cooling water temperature of the condenser, using the case study of pyrolysis of biomass waste from coconut trunk sawdust. Pyrolysis was conducted at a temperature of 400°C for 2.5 hours, varying the flow rate of the cooling water in the condenser (1, 2, 2.5, 3, and 3.5 liters/minute)and the temperature of the cooling water (10°C, 20°C, 25°C, and 30°C). A multivariable nonlinear mathematical model was obtained, relating the yield of liquid smoke (y; %) to the water temperature parameter (x1) and the flow rate of the cooling water in the condenser (x2), which is expressed as y = 6.68 + 1.89x1 – 0.04x1² – 0.41x1x2 + 13.06x2 – 0.89x2². It was concluded that the optimal condensation conditions consist of a flow rate and cooling water temperature of 2 liters/minute and 20°C, respectively, yielding a maximum of 36% liquid smoke, 33% charcoal, and a minimum mass loss of 31%. Based on the coefficient values in the obtained mathematical model, it can also be concluded that the more dominant parameter affecting the yield of liquid smoke is the flow rate of the cooling water in the condenser, with a coefficient value of 13.06. An effective condensation system can enhance the conversion efficiency of pyrolysis vapour into liquid smoke and minimize potential pollution, demonstrating significant potential in processing biomass waste into valuable products, such as liquid smoke and charcoal, while being more environmentally friendly and energy-efficient.